Satisfaction with personal and environmental quality of life: a black South African informal settlement perspective - MS Westaway; T Gumede (AOSIS, 2001)
A study was conducted with 487 black adult residents of a South African informal settlement (151 men and 336 women) to ascertain satisfaction with personal and environmental quality of life. It was hypothesised that: (1) health status and life satisfaction were the underlying dimensions of personal quality of life (PQOL); (2) health status and life satisfaction were more strongly associated with PQOL than environmental quality of life (EQOL); and (3) life satisfaction and satisfaction with EQOL were positively related. Seventy per cent of respondents rated their health as good or better. Age, schooling and employment status were significantly related to health, life satisfaction and PQOL. Reliability (internal consistency) coefficients were 0.77 for the 5-item life satisfaction scale and 0.82 for the 12-item EQOL measure. Factor analysis showed that safety and security was the major unmet service need. Health status and life satisfaction explained 38% of the variance in PQOL; health status explained only 4% of the variance in EQOL. Life satisfaction was significantly related to EQOL (r = 0.16, p = 0.01). The results provided support for all three hypotheses. It was concluded that the life satisfaction and EQOL measures had good reliability; there was a definite need for a safety and security programme; and good health was a more important predictor of PQOL than EQOL.